Experience at Russian State Agrarian University – Moscow Timiryazev Agricultural Academy on introduction and integration of precision agriculture technology - Zhelezova, Sofya V.; Berezovsky, Egor V.; Belenkov, Alexey I. (Acta Agraria Debreceniensis, 2012)
Traditional and precision agriculture technologies are compared on the basis of the field experiment. Problems of soil and crop survey and mapping are discussed.